News and News Translation: History and Strategies - Seyyed Shahram Hosseini Shafia, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Translating is a complex process because it involves a simultaneous processing the source language texts and maintaining neutrality. The translating news is more complicated because in translating news, factors such as connotation, perspective, and ideology associated with news production makes the process more complex than more conventional practices of translating. The present study provides information about translation, news and news translation, translation strategies, and previous research related to this. during news translation, news may be edited, summarized, passed on via another language, edited again, transferred into the news agency language, adapted to the house style of a particular publication, and shortened to conform to space limits. All the above-mentioned processes happen at various stages when linguistic, cultural, and national boundaries are crossed. Translation problems on the part of the translator. The use of different strategies in translation of idioms shows the diverse ways of treatment of this interesting and difficult part of language. Idioms show the uniqueness of the language and culture in which they are originated and, therefore, the strategies for their translation need careful consideration and the translators need deep knowledge of the source and target languages and cultures.